Adherence to a Mediterranean Diet and Risks of Alzheimer and Parkinson Diseases: A Systematic Review of Population-Based Studies - Sukshma Sharma; Alessandro Gialluisi; Maria Benedetta Donati; Giovanni de Gaetano; Vittorio Maglione; Licia Iacoviello; Marialaura Bonaccio (Proceedings)
Background and objectives: Diet is suggested as a major modifiable risk factor for neurodegenerative diseases, but there is conflicting and inadequate evidence regarding whether adherence to a Mediterranean diet (MD) is associated with lower risks of Alzheimer Disease (AD) and Parkinson Disease (PD). We performed a systematic review of available population-based studies to disentangle the association between MD and risk of AD or PD. Methods: PubMed, MEDLINE, Embase and Scopus were searched for relevant articles published from inception until April 2023. Only observational cohort studies, prospective studies, and case–cohort studies were included to explore the longitudinal association between adherence to an MD and the risk of AD and PD. Studies with adult participants (>18 years old) were included if they explored and reported results on MD, along with other dietary patterns, and examined MD using the following definitions: ‘Medi Score diet’ and ‘alternate Mediterranean diet index (aMED diet)’. Results: A total of three studies (two longitudinal and one case–control) on AD were identified out of 1233 records, and five studies on PD (three longitudinal and two case–control) out of 320 records were identified. For AD, all three studies reported an association between a higher adherence to an MD and a lower risk of AD, with values ranging from 9% (Hazard ratio, 0.91; 95% confidence interval, 0.83–0.98; p = 0.015) to 54% (Hazard ratio = 0.46, 95% CI 0.26, 0.79, p = 0.01). For PD, three out of five studies reported that a higher adherence to MD was associated with a lower risk of PD, with values ranging from 11% (Hazard ratio = 0.89; 95% CI 0.74–1.07) to 46% (Hazard ratio = 0.54; 95% CI 0.30–0.98). Conclusions/Discussion: The overall longitudinal findings suggested that a high adherence to an MD was inversely associated with the risks of AD and PD, and might be beneficial for nutrition strategies and clinical treatment. However, further epidemiological studies are warranted to increase the generalizability of the findings and to better understand the longitudinal associations for efficient prognosis of AD and PD.